Effects of slalom switch, okubuuka, and kykkaa training on kids’ athletics level 2 skills among children aged 8-11 years - Kardi, Ipa Sari; Ansar CS; Anwar, Khairil; Marpaung, Hakim Irwandi; Hasan, Baharuddin (Journal Sport Area, 2026)
Background: Early childhood is a critical period for developing fundamental motor skills and physical fitness; however, despite the widespread implementation of kids’ athletics programmes, limited research has examined the combined effects of specific training models, such as Slalom Switch, Okubuuka, and Kykkaa, within a structured intervention to improve multiple physical fitness components in children. Objectives: This study aimed to examine the effects of a 12-week Kids’ Athletics Level 2 training programme on physical fitness in children aged 8-11 years. Methods: A quasi-experimental one-group pretest–posttest design was employed involving 40 elementary school students selected through purposive sampling. The intervention was conducted three times per week. Physical fitness was assessed using the Indonesian Student Fitness Test (TKSI), including coordination, accuracy, strength, agility, and cardiovascular endurance. Data were analysed using paired sample t-tests. Results: The results showed significant improvements across all variables (p < 0.05), with the largest increases observed in coordination (+57.14%) and strength (+50%), followed by accuracy (+50%), endurance (+15.25%), and agility (+10.23%). Conclusion: In conclusion, the Kids’ Athletics Level 2 training model may be effective in enhancing multiple components of physical fitness in children. However, the absence of a control group limits causal interpretation, and further studies using controlled experimental designs are recommended.